1990
DOI: 10.1128/iai.58.4.961-969.1990
|View full text |Cite
|
Sign up to set email alerts
|

New mouse models for chronic Cryptosporidium infection in immunodeficient hosts

Abstract: Cryptosporidium sp. causes fulminant diarrhea and chronic infection in immunocompromised, particularly human immunodeficiency virus-infected, persons. The lack of in vitro cultivation and a suitable animal model has limited development of effective treatment. We describe two new mouse models of chronic symptomatic cryptosporidiosis in adult athymic mice and in T-cell subset-depleted mice. A progressive infection, fatal within 4 months, occurred in most adult athymic mice; a few developed stable infections. Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 32 publications
3
59
0
1
Order By: Relevance
“…The mice were necropsied 24 h after the final treatment. Gross and histologic changes observed in all groups were similar to those previously described for persistent cryptosporidiosis in nude mice (16,24). The predominant gross findings included icterus, multifocal areas of hepatic necrosis, diffuse hepatic congestion, hypertrophy and thickening of the gallbladder and common bile duct, and intestinal distention in seven mice (5 of 13 isotype control MAbtreated and 2 of 6 nontreated mice).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The mice were necropsied 24 h after the final treatment. Gross and histologic changes observed in all groups were similar to those previously described for persistent cryptosporidiosis in nude mice (16,24). The predominant gross findings included icterus, multifocal areas of hepatic necrosis, diffuse hepatic congestion, hypertrophy and thickening of the gallbladder and common bile duct, and intestinal distention in seven mice (5 of 13 isotype control MAbtreated and 2 of 6 nontreated mice).…”
supporting
confidence: 81%
“…Assessment of therapeutic protocols has been slowed by the absence of a convenient animal model of persistent cryptosporidiosis (5-7). Ungar et al have recently demonstrated that persistent infection can be established in immunodeficient nude mice experimentally infected with C. parvum (24). Our hypothesis is that neutralizing antibodies to sporozoite and merozoite surface antigens will resolve persistent cryptosporidial infections in immunodeficient hosts.…”
mentioning
confidence: 83%
“…The role of cell-mediated immunity in the recovery of mice from Cryptosporidium infection is well documented and the importance of T-lymphocytes, particularly CD4+ T cells has been determined (8,10,16,17,23,24). On the other hand, the significance of CD8+ T cells remain unclear and is probably generally underestimated (25).…”
Section: Discussionmentioning
confidence: 99%
“…Aguirre et al (1994) observed that mice with MHC II de®ciency and therefore lacking CD4 T-cells failed to control C. parvum infection whereas MHC I-de®cient mice, which lack CD8 T-cells, were no more susceptible to infection than normal mice. Similarly, antibody-mediated depletion of CD4 T-cells from immunocompetent mice or SCID mice reconstituted with functional lymphocytes signi®cantly impaired the development of immunity while, in contrast, depletion of CD8 T-cells had either only a moderate or no effect on resistance (Ungar et al 1991, Ungar et al 1990. In studies with C. muris, it was reported that immunity to infection could be adoptively transferred to SCID mice with spleen or mesenteric lymph node cells from immunocompetent mice recovered from infection, but adoptive immunization was abrogated when the donor cells were depleted of CD4 T-cells .…”
Section: T-cells and Control Of Infectionmentioning
confidence: 99%